Tree of life 1 - Unidentified artist (Colorado State University. Libraries, 1980)
Artisans worldwide have crafted trees of life designs containing various plants and animals. These Kuna trees of life are filled with monkeys. This mola is made in colors commonly used in molas that are worn by Kuna women.
This item was part of an exhibition at the Avenir Museum of Design and Merchandising titled Kuna Molas: Sewn Stories and the Interplay of Tradition and Change, August 18, 2014-July 31, 2015.
Cotton; 3 layers (maroon, orange, black); reverse and direct appliqué, embroidery.
Keywords: Molas -- Panama; Appliqué -- Panama; Embroidery -- Panama